Seroprevalence of Toxoplasma gondii in Camels in Tamboul area, Sudan - H. M, Elias; M.B., Tagwa; H.S., Abdalla (Journal of Veterinary Medicine and Animal Production, 2021)
The importance of meat in the diet is that it is Toxoplasma gondii is an obligate intracellular protozoan parasite that infects almost all bloodedanimals and man (Dubey et al., 2013). The definitive host is cat and the intermediate hosts are mammals and birds (Dubey, 2004). The source of transmission is the ingestion of food contaminated by cat faces, raw or undercooked meat. In Sudan, many people consume raw, uncooked camel livers. Also, camel herders are accustomed to drink raw, unboiled camel milk.